Prediction factors of the autologous arteriovenous fistula complications for hemodialysis - Michel Planche Moreno; Celso Suárez Lescay; Victoria Frómeta Ríos (Centro Provincial de Información de Ciencias Médicas, 2016)
A retrospective, cross-sectional and descriptive study was carried out, to determine the prediction factors about the emergence of complications in 300 patients with a created arteriovenous fistula, assisted in the Angiology and Vascular Surgery Service of "Saturnino Lora" Teaching Provincial Hospital in Santiago de Cuba during the triennium 2012 - 2015. Among the main results the female sex (52.7%), the 51-60 age group (55.6%), hypertension and diabetes mellitus prevailed as the most common risk factors, as well as the AVF complication at wrist level, mainly in females (34.2%). It was concluded that the arteriovenous fistula complications depend on the presence or not of risk factors that can be a negative marker that affects the patient's life quality and per se determine the survival time.